Peran Tasawuf dalam Dunia Pendidikan di Tengah Krisis Spiritualitas Masyarakat Modern - Danissa Selvita Fauziah; Rifki Rosyad (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the role of Sufism in the world of education in the midst of the spiritual crisis of modern society. This study uses a qualitative approach by applying the descriptive-analytical method. The results and discussion in this study show that Sufism in educational studies is seen as a process of inner growth and manifestation of spirituality in real life. This study concludes that the role of Sufism in the world of education in the midst of the spirituality crisis of modern society is considered necessary, especially if you look at the times that are driven by the very rapid progress of science and technology in the modern era.